Determination of Pb(II) Ions in Water by Fluorescence Spectroscopy Based on Silver Nanoclusters - Luca Burratti; Valentin Maranges; Michele Sisani; Eziz Naryyev; Fabio De Matteis; Roberto Francini; Paolo Prosposito (Chemosensors, 2022)
In this work, a method to determine Pb(II) ions in model water is presented; the method is based on the fluorescence emission of a silver nanoclusters (AgNCs) colloidal solution, which is sensitive to lead ions. The presence of Pb(II) ions causes a photoemission enhancement of the AgNCs solution dependent on the pollutant concentration. The functional dependence is logarithmic in the range from 2.5 to 40 µM, and through the linearization of the calibration points, a linear function is determined and exploited for the extrapolation of the test Pb(II) concentrations with a precision estimated by relative standard deviation (RSD) ranging from 21% to 10% from the highest to the lowest Pb(II) quantity, respectively. Finally, inductively coupled plasma–optical emission spectroscopy (ICP-OES) successfully validated the described method. The accuracy of the method is also studied for intentionally polluted mineral waters, revealing the same trend of the model water: the lower the concentration, the higher the precision of the method.